Curriculum track choice and high school dropout likelihood - Mohd Kamalludeen, Rosemaliza; Miyazak, Yasuo (2013)
This study attempts to investigate the influence of curriculum track choices, namely academic, career and technical education, dual enrollment, and general curriculum, on dropout likelihood, while controlling for predictors that predict both curriculum track choices and dropout likelihood among high school students. Analysis will be conducted via HGLM due to the nested data structure of Education Longitudinal Study 2002 (ELS) that has student-level and school-level predictors. Other predictor variables include academic background, academic and career aspiration, school-sponsored activities participation, demographic indicators and school-level predictors. The suspected confounding relationship between these predictors in explaining curriculum choice influences on dropouts might enlighten educators and counselors in channeling students to the most suitable curriculum tracks that will lead to successful high school careers.